2010
DOI: 10.1002/ardp.201000167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐Hepatitis B Virus Activity of a Novel Class of Thiazolylbenzimidazole Derivatives

Abstract: Recently, heterocyclic benzimidazole derivatives have been investigated and validated as a promising class of antiviral agents. In this paper, a series of novel thiazolylbenzimidazole derivatives was synthesized and evaluated for their anti-hepatitis B virus (HBV) activity and cytotoxicity on the HepG2.2.15 cell line. Afterwards, the preliminary structure-activity relationship (SAR) was discussed. Compound 8b, with IC(50)  = 1.1 µM and SI > 90.9, was the most promising compound and could be selected as a bench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Fur ther more, benzimidazole moiety is a crucial template in medicinal chemistry because of its wide variety of reported biological and pharmacological activities, some of which include anticancer 11 , antimicrobial 12 , antitumor 13 , antimalarial 14 ,anti-HIV 15 , anti-inflammatory 16 , antitubercular 17 , anthelmintic 18 , anticonvulsant 19 , antioxidant 20 , anti-ulcer 21 , anti-HBV 22 , among others. The pharmacological investigation showed that the antagonism of Ang II-induced pressure response by oral administration of a series of benzimidazole hybrid was obviously superior to that of clinical drug standard used.…”
Section: -9mentioning
confidence: 99%
“…Fur ther more, benzimidazole moiety is a crucial template in medicinal chemistry because of its wide variety of reported biological and pharmacological activities, some of which include anticancer 11 , antimicrobial 12 , antitumor 13 , antimalarial 14 ,anti-HIV 15 , anti-inflammatory 16 , antitubercular 17 , anthelmintic 18 , anticonvulsant 19 , antioxidant 20 , anti-ulcer 21 , anti-HBV 22 , among others. The pharmacological investigation showed that the antagonism of Ang II-induced pressure response by oral administration of a series of benzimidazole hybrid was obviously superior to that of clinical drug standard used.…”
Section: -9mentioning
confidence: 99%
“…• Benzimidazole derivatives, 61 and 62, were the most promising compounds with high antiviral potency (IC 50 = 0.9 and 0.7 μM, respectively), and remarkable selectivity index (SI > 1111 and 714, respectively), which were selected for further evaluation as novel HBV inhibitors. as a lead compound for further investigation [148]. In order to develop potent anti-HBV inhibitors, a series of potent HBV inhibitors of 1-isopropylsulfonyl-2-amine benzimidazole derivatives were also designed, synthesized and evaluated for their anti-HBV activity and cytotoxicity in the HepG2.2.15 cells.…”
Section: Key Discovery In Anti-hbv Researchmentioning
confidence: 99%
“…Benzimidazole derivatives have attracted considerable attention from researchers because their bioactive and pharmaceutical properties. Many members of this family are widely used as anticonvulsant, anti-fungal, analgesic, antimicrobial, anti-histaminic and hypnotic or anti-inflammatory agents (Ayhan-Kılcıgil et al, 2007;Soderlind et al, 1999;Luo et al, 2011;Walia et al, 2011;Navarrete-Vá zquez et al, 2001). Benzimidazolone derivatives also find commercial use as dyes for acrylic fibres.…”
Section: Chemical Contextmentioning
confidence: 99%